Effects of barium graded doses on redox status, membrane bound ATPases and histomorphological aspect of the liver in adult rats. (22nd November 2017) - Elwej, Awatef; Chaabane, Mariem; Ghorbel, Imen; Chelly, Sabrine; Boudawara, Tahia; Zeghal, Najiba
Abstract: Nowadays, liver diseases constitute a major health problem in the world. The objective of the present study was to elucidate the hepatotoxicity induced by barium chloride (BaCl2 ) administered at graded doses in order to evaluate redox state and membrane-bound ATPases in the liver of adult rats. Our results showed, after 21 days of treatment with barium at doses 67 150 and 300 ppm, an increase in hepatic biomarkers such as AST, ALT and GGT activities and in bilirubin and albumin levels. A significant increase in MDA, LOOHs, H2 O2, AOPP and PCO levels in liver of treated rats with graded doses of BaCl2 was also observed suggesting the implication of oxidative stress with a significant relation between dose and response. Moreover, LDH activity increased in plasma and decreased in liver of all treated groups. Antioxidant activities of glutathione peroxidase and catalase decreased, especially with the highest dose of barium, indicating a failure of antioxidant system defense. Additionally, the activities of Na + K + -ATPase and Mg 2+ -ATPase significantly decreased in all treated groups. Our biochemical findings were supported by histological observations. These results highlight the subchronic hepatotoxicity of barium.